Impact of interhospital transfer vs. direct admission on acute ischemic stroke patients: A subset analysis of the COMPLETE registry - Hassan, Ameer E.; Zaidat, Osama O.; Nanda, Ashish; Atchie, Benjamin; Woodward, Keith; Doerfler, Arnd; Tomasello, Alejandro; Fifi, Johanna T. (Frontiers in Neurology, 2022)
BACKGROUND Efficacy of thrombectomy treatment in acute ischemic stroke large vessel occlusion (AIS-LVO) patients is time dependent. Direct admission to thrombectomy centers (versus interhospital transfer) may reduce time to treatment and improve outcomes. In this subset analysis of the COMPLETE registry, we compared outcomes between direct to thrombectomy center (Direct) versus transfer from another hospital to thrombectomy center (Transfer) in AIS-LVO patients treated with aspiration thrombectomy. METHODS COMPLETE was a prospective, international registry that enrolled patients from July 2018 to October 2019, with a 90-day follow-up period that was completed in January 2020. Imaging findings and safety events were adjudicated by core lab and independent medical reviewers, respectively. Pre-defined primary endpoints included post-procedure angiographic revascularization (mTICI≥2b), 90-day functional outcome (mRS 0-2), and 90-day all-cause mortality. Planned collections of procedural time metrics and outcomes were used in the present post-hoc analysis to compare outcomes between transfer and direct patient cohorts. RESULTS Of 650 patients enrolled, 343 were transfer (52.8% female; mean [SD] age, 68.2 [13.9] years) , and 307 were direct (55.4% female; 68.5 (14.5) years admit. Median onset-to-puncture time took longer in the transfer versus direct cohort (5.65 versus 3.18 hours: 2.33 hours difference), respectively; p<0.001). There was no significant difference in successful revascularization rate, mTICI≥2b (88.3% and 87.3%), sICH at 24 hours (3.8% and 3.9%), median length of hospital stay (7 and 6 days), and 90-day mortality (16.9% and 14.0%) between transfer versus direct patients, respectively. However, achieving 90-day functional independence was less likely in transfer compared with direct patients (mRS 0-2 was 50.3% versus 61.7%, p=.0056). CONCLUSION In this subset analysis of the COMPLETE registry, direct to thrombectomy center was associated with significantly shorter onset-to-puncture times, and higher rates of good clinical outcome across different geographies. Additional research should focus on AIS-LVO detection to facilitate direct routing of patients to appropriate treatment centers. CLINICAL TRIAL REGISTRATION INFORMATION https://clinicaltrials.gov; Unique identifier: NCT03464565